Total hip arthroplasty and cardiovascular complications: a review - Taheriazam A; Saeidinia A; Keihanian F (Dove Medical Press, 2018)
Afshin Taheriazam,1 Amin Saeidinia,2 Faeze Keihanian3,4 1Department of Orthopedics Surgery, Tehran Medical Sciences Branch, Islamic Azad University, Tehran, Iran; 2Mashhad University of Medical Sciences, Mashhad, Iran; 3Cardiology Department, Imam Reza and Ghaem Hospitals, Faculty of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran; 4Pharmaceutical Research Division, Booali Research Center, Mashhad University of Medical Sciences, Mashhad, Iran Abstract: Most adverse events following total hip arthroplasty (THA) are uncommon and preventable or treated easily as expected. Adverse effects related to any major surgical procedure, including anesthesia, performing with other medical problems, drugs, and allergic reactions, might also occur. Potential cardiovascular complications are known to occur during or following THA and will be reviewed here. Complications can be categorized as myocardial infarction, cardiac arrest, thromboembolism, and so on. Special considerations in cardiovascular procedures are also reviewed in this paper. Keywords: myocardial infarction, total hip replacement, post-surgical adverse events, hip fracture